Vocabulary Enhancement through Presentation, Practice, Production(PPP) Method in the Rural EFL Classrooms - Katemba, Caroline Victorine (LPPM Universitas Advent Indonesia, 2022)
The purpose of this research was to look into how to improve students' vocabulary achievement by using the Presentation, Practice, and Production method. This study used both quantitative research and an experimental design. In this study, 68 seventh-grade students from SMP Negeri in Bandung Barat participated. They were split into two groups: the control and the experimental. Both groups received the same pre-test. The Presentation, Practice, and Production method was taught to the experimental group, while the traditional method was taught to the control group. Statistical analysis of the data revealed a significant difference in enhancement between the experimental and control groups. Both groups improved, but the control group did not outperform the experimental group. The researcher recommended that the teacher teach vocabulary using the Presentation, Practice, Production method because it is effective in increasing student vocabulary in rural EFL classrooms.